Annealing Temperature Effect on Phase Transition and Thermoelectric Properties of Doped Zinc-Antimony - Mohsen Mankhi Alrkaby; Ahmed Radhi Salim; Hisham Mohammed Ali Hasan (Eximia, 2025)
The intermetallic compound ZnSb is a (II-V) narrow gap semiconductor with interesting thermoelectric properties. Electrical resistivity, Hall coefficient and thermal conductivity were measured from 300 up to 600 K on Cu once and Ag-doped samples with a concentration of 0.5%, which were the annealed powder was sinterable at 50 MPa in a uniaxial hot press. The work confirms a significant improvement of the thermoelectric Figure-of-merit, ZT, 61% for Ag doping and 143% for Cu doping. The optimum doping level is near 0.5 at.% Cu and results in ZT values around 0.916 at 600 K. A significantly lower resistivity, which is linked to a higher concentration of hole charge carriers, is the cause of the improvement. The intrinsic impurity band of ZnSb is said to be enhanced by Cu replacing trace amounts of Zn (around 0.2 at.%) in the crystal structure. It was discovered that excess Cu was segregated at grain borders.